Algorithmic module for investment program formation within the decision support system of the company development - Volodymyrovna, Moskalenko Valentina; Kachanova, Svitlana Igorivna (Vestnik Nacionalʹnogo tehničeskogo universiteta "HPI". Seriâ Sistemnyj analiz, upravlenie i informacionnye tehnologii (Online), 2018)
The article reviews modern methods of investment portfolio formation and approaches to the development of investment decision support systems. Therefrom it is concluded that such systems are intended for information and analytical support of the process of forming of portfolios of investment in other companies’ projects or in securities issued by different entities. Formation of such portfolios does not take into account the impact of a company’s investment on this company strategic development. The article offers the approach of forming an investment portfolio at the company engaged both in external and internal investment. The company development projects (internal investment) and other companies’ securities (external investment) are considered to be investment values for investing the company’s own funds. The choice of investment objects is carried out based on the utility function. The utility function is based on the criteria of maximization of the investment yield and the degree of impact of an investment object on strategic development, and minimization of the investment risk. The article offers the business process of the investment program formation, which contains the following main procedures: investment resources distribution between investment portfolios; forming a portfolio of investment projects that will be implemented within the company development program; formation of a portfolio of foreign investments in projects of other enterprises; formation of a portfolio of securities; formation of a common company investment portfolio as the aggregate of the three above. This business process is realized within the scope of the algorithmic module of the decision support system for the company development. The use of such a module is followed by formation of the company investment portfolio. This decision support system is a part of the Enterprise Performance Management Systems, which are designed to provide information and analytical support to processes of the company strategic management.